2014
DOI: 10.3727/096368913x664847
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage of Rat Hepatocyte Spheroids

Abstract: Cell-based therapies for liver disease rely on a high-quality supply of hepatocytes and a means for storage during transportation from site of isolation to site of usage. Unfortunately, frozen cryopreservation is associated with unacceptable loss of hepatocyte viability after thawing. The purpose of this study was to optimize conditions for cold storage of rat hepatocyte spheroids without freezing. Rat hepatocytes were isolated by a two-step perfusion method; hepatocyte spheroids were formed during 48 h of roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
2
3
0
Order By: Relevance
“…However, no marked differences in findings were noted between groups C and D on examining HE-stained high-magnification images. Therefore, an additional examination with electron microscopy was performed, which revealed that while the structure in the hepatocytes was maintained in group D, there was apparent denaturing of the hepatocyte structure in group C. The low-temperature damage observed on electron microscopy has also been previously reported [15], showing findings compatible with our own. Tullius et al [16] reported that the accumulation of intravascular and interstitial crystals and the formation of extracellular and intracellular ice in the organ tissue were the main causes of freezing injury in organs and were particularly harmful to the vascular system.…”
Section: Discussionsupporting
confidence: 89%
“…However, no marked differences in findings were noted between groups C and D on examining HE-stained high-magnification images. Therefore, an additional examination with electron microscopy was performed, which revealed that while the structure in the hepatocytes was maintained in group D, there was apparent denaturing of the hepatocyte structure in group C. The low-temperature damage observed on electron microscopy has also been previously reported [15], showing findings compatible with our own. Tullius et al [16] reported that the accumulation of intravascular and interstitial crystals and the formation of extracellular and intracellular ice in the organ tissue were the main causes of freezing injury in organs and were particularly harmful to the vascular system.…”
Section: Discussionsupporting
confidence: 89%
“…Based on a previous study, a similar effect of cold preservation of lower density and total amount (1 × 10 6 cells/mL, 2 × 10 7 cells in total) of rat hepatocyte spheroids in a custom serum‐free medium and UW solution was observed . The conclusion in that paper was based on viability and albumin production.…”
Section: Discussionsupporting
confidence: 56%
“…Based on a previous study, a similar effect of cold preservation of lower density and total amount (1 × 10 6 cells/mL, 2 × 10 7 cells in total) of rat hepatocyte spheroids in a custom serum-free medium and UW solution was observed. 29 The conclusion in that paper was based on viability and albumin production. The experiments were performed in serum-free medium supplemented with additives, but ammonia clearance ability after cold storage decreased quickly.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore it is conceivable, that a high cellular loss of ATP during liver cell transportation in suspension [14] is responsible for the lack and/or delayed urea formation. In the same line of evidence Liu et al clearly showed that cold storage of cells reduces the metabolic testing capacity, including the ammonia detoxification capacity [64]. Based on these data, it seemed that hepatocytes recover faster in 3D than in 2D cultures, suggesting a lack of additional cofactors necessary to fully transform ammonia into urea.…”
Section: Discussionmentioning
confidence: 93%